Can AI Make Decisions About Clinical Trials? A Look at Autonomy, Ethics, and the Future of Drug Development - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2021)
The integration of Artificial Intelligence AI into healthcare is rapidly transforming medicine, and clinical trials are no exception. The question of whether...
Keywords: Drug Discovery; Digital Health; Artificial Intelligence; Healthcare Innovation; Patient Care